The Changing Needs for Higher Education Organizations Structure in Vietnam: Evidence from Japanese, Taiwanese, and Thai Universities - Minh-Quang Duong (Journal of Education and Learning (EduLearn), 2013)
Organizational change is the process of changing the structure of the organization and the attitudes of members in the organization. During the last decade, both Vietnamese social and educational organizations have slowly changed in their organizational structure as a barrier to the development in the era of globalization and internationalization in Vietnam. This paper is an attempt to discuss the factors which affect Vietnamese higher educational organization. Discussions on the viewpoint of higher educational organization structure of Japan, Taiwan, and Thailand. Furthermore, this paper will contribute to improve educational management, and serve as a useful reference for future higher education’s school mergers.